Optogenetic stimulation of the basolateral amygdala accelerates acquisition of object-context associations - DiFazio, Lauren E. (Behav Neurosci, 2021)
The basolateral complex of the amygdala (BLA) is capable of modulating memory and is thought to do so via projections to regions such as the hippocampus. The present study used optogenetic stimulation of glutamatergic projection neurons in the BLA as rats learned object-context associations during a well-studied hippocampus-dependent memory task. Relative to a control condition, optogenetic BLA stimulation resulted in accelerated acquisition of object-context associations when stimulation was delivered following correct choices but not when it was delivered during the intertrial interval. These results extend prior examples of amygdala-mediated memory enhancement to a canonical example of hippocampus-dependent memory and provide opportunity for future dissection of amygdalar modulation of object-context associative memory.